Beyond Borders: Jean Gerson’s Conciliarism in Late Medieval Spain - Kern, Darcy (Renaissance and Reformation / Renaissance et Réforme, 2019)
In recent years there has been renewed interest in conciliarism, the belief that the authority of the universal church resides in an ecumenical council, not the pope, though the perception remains that conciliarism had a negligible impact in Iberia. One way to better understand the evolution of conciliar thought in the Spanish kingdoms is by looking at the circulation of the works and ideas of the French conciliarist Jean Gerson (1363–1429). Though a complete reconstruction of Gerson’s circulation is impossible, one can offer an initial overview of his impact in the Spanish kingdoms not simply by counting manuscripts or incunabula, as valuable as that is, but by thinking broadly about networks of exchange and dissemination. Gerson’s works came to Spain through the church councils, trans-Pyrenees Carthusian networks, monastic reformers, printers and printing houses, mendicant reformers, and the library of the University of Salamanca.